Not EF skills but play with real toys prevents screen time tantrums in children - Gavrilova, Margarita; Veraksa, Nikolay (Frontiers in Psychology, 2024)
Limiting children’s screen time has become a new parenting challenge. Due to the high attractiveness of media and digital devices, many children experience painful transitions in screen time to other activities. Screen time tantrums is a new concept that describes children’s negative affect screen time limits. Knowing the factors that increase children’s negative reactions will be helpful in parents and educators practice to prevent screen time tantrums or enrich children’s nondigital activities, making them attractive alternatives to the media. Based on theoretical insights into the coping mechanisms of frustration and anger in preschool children, this study was aimed to explore the effects of executive functions skills, family activities, and children’s play behavior with real toys on screen time tantrums. Sample included 654 caregiver-child pairs (M children age = 70.3 months, SD = 4.02). Results confirmed the hypothesis that play behavior with real toys is a stronger preventor of screen time tantrum than EF skills. The findings suggest that supporting play activity in preschool children might help them to avoid strong negative affects due to screen time limitation. The results of this study may be also considered as a support for the theoretical assumptions that play can be considered as a universal way of coping with frustration and anger in childhood.